Sawtooth Variation of Horizontal Component with Solar Wind Conditions at High-Latitude - Devi, Rajni; Saini, Shailendra; Dhar, Ajay; Gwal, A.K. (2017)
We have examined three well-defined events of sawtooth oscillations in solar wind and magnetic field at high-latitude. For this study we have taken data of H component collected from digital fluxgate magnetometer at localized region of “MAITRI” (geom. 62S, 52.8E), Antarctica during storms of August, October and November 2003. The observed H component variation is compared with the plasma parameters (proton density N and speed ν) and vertical component of Interplanetary Magnetic Field (IMF), magnetic activity. Results show that before storm sudden commencement (SSC) time the magnitude of H component, auroral electrojet index, proton density and speed, IMF shows smooth variation but after SSC of first storm, these all parameters shows fluctuations and at 20:00UT it starts to increase, but during second storm occurred next day, the magnitude of H component indicates large fluctuations and it increases rapidly. During all three events, nearly simultaneous solar energetic particles, IMF enhancements and magnetic field variations occurred for each sawtooth cycle. Geomagnetic H component data at high latitude also show a global H increase simultaneously with solar wind particles, IMF and auroral elecrojet AE indices generally show increases at each sawtooth cycle. All these are what is expected if solar wind pressure enhancements impacted the magnetosphere at times appropriate to have caused the onset of each sawtooth cycle. Finally we are enabled the solar wind and IMF has been predicted swatooth variation of H component during magnetic storm cause intense geomagnetic storm.